2006
DOI: 10.1055/s-2006-926607
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Tendinous Ossification with Concomitant Tendonitis and Bursitis - Ultrasound Grey-Scale and Colour Doppler Findings

Abstract: A case report of a 62-year-old man with a 20-year history of tendon problems, who presented with a swollen and tender left Achilles tendon. Ultrasound (US) revealed a 2 x 1 x 0.9 cm intra-tendinous substance with acoustic shadowing. On a radiogram, ossification was found. Colour Doppler activity was present in both the bursa and the tendon. A US-guided injection of 40 mg Depomedrol was applied into the retrocalcaneal bursa. On follow-up two months later, the patient had no symptoms and US showed total regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Ultrasound is not necessary to confi rm a diagnosis but may reveal signs of Achilles tendinopathy, bursitis and ossifi cation of the insertion of the Achilles tendon. 126,127 Similarly, MRI is rarely used but may assist in differentiating between normal and abnormal retrocalcaneal bursae. A recent case-control study indicated that retrocalcaneal bursae larger than 1 mm anteroposteriorly, 11 mm transversely, or 7 mm dorsoplantarly can be considered abnormal.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…Ultrasound is not necessary to confi rm a diagnosis but may reveal signs of Achilles tendinopathy, bursitis and ossifi cation of the insertion of the Achilles tendon. 126,127 Similarly, MRI is rarely used but may assist in differentiating between normal and abnormal retrocalcaneal bursae. A recent case-control study indicated that retrocalcaneal bursae larger than 1 mm anteroposteriorly, 11 mm transversely, or 7 mm dorsoplantarly can be considered abnormal.…”
Section: Assessment and Diagnosismentioning
confidence: 99%